The influence of fly ash and neutral sodium silicate on concretes submitted to sulfuric acid attack. (November 2022) - da Silva Munhoz, Guilherme; Edilson Gomes Dobrovolski, Mateus; Leandro Nenevê, Bruno; Luiz Dias, Roberto; Pereira Godinho, Jayson; Henrique Farias de Medeiros, Marcelo
Highlights: Wastewater treatment plants are subjected to H2 SO4 attack due to biogenic corrosion. The sulfuric acid attack is decelerated in samples with high calcium contents. The Na2 SiO3 hydration limited the calcium content, but densified the microstructure. The fly ash hydration (pozzolanic reaction) also reduced the calcium availability. Concurrent hydration mechanisms impaired the Na2 SiO3 and the fly ash performance. Abstract: The service life of wastewater treatment plants is often impaired by the biogenic deterioration caused by sulfuric acid (H2 SO4 ). This study used fly ash (as a Portland cement replacement) and different contents of neutral sodium silicate (0%-10%) as mitigating solutions. One group was immersed in lime-saturated water for 182 days, and the other was submitted to a 0.5% H2 SO4 solution for the same interval. The microstructural analysis (SEM/XRD) confirmed the consumption of calcium-based compounds during the pozzolanic reaction, the Na2 SiO3 hydration, and the H2 SO4 attack. The neutralized depths measured after spraying phenolphthalein reiterated this trend. The H2 SO4 front progressed inwards, promoting gradual peeling and the formation of gypsite. The slow diffusion of H2 SO4 did not impair the early-age compressive strength, but the depletion of the alkaline reserve hindered the results in the long term. Therefore, Na2 SiO3 was not a viable mitigating solution against the H2 SO4 attack, contrary to fly ash.